Damaged DNA-binding Protein 1 (DDB1) Interacts with Cdh1 and Modulates the Function of APC/C(Cdh1) - Lv, Xiao-Bin (American Society for Biochemistry and Molecular Biology, 2010)
APC/C(Cdh1) plays a key role in mitotic exit and has essential targets in the G(1) phase; however, these mechanisms are poorly understood. In this report, we provide evidence that damaged DNA-binding protein 1 (DDB1) is capable of binding the WD40 domains of Cdh1, but not of Cdc20, through its BPA and BPC domains. Moreover, cells lacking DDB1 exhibit markedly elevated levels of the protein substrates of APC/C(Cdh1). Depletion of DDB1 in mitotic cells significantly delays mitotic exit, which demonstrates that the interaction between DDB1 and Cdh1 plays a critical role in regulating APC/C(Cdh1) activity. However, cells depleted of Cdh1 demonstrated no change in the UV-induced degradation of Cdt1, the main function of DDB1 as an E3 ligase. Strikingly, the APC/C(Cdh1) substrate levels are normal in cell knockdowns of Cul4A and Cul4B, which, along with DDB1, form an E3 ligase complex. This finding indicates that DDB1 modulates the function of APC/C(Cdh1) in a manner independent on the Cul4-DDB1 complex. Our results suggest that DDB1 may functionally regulate mitotic exit by modulating APC/C(Cdh1) activity. This study reveals that there may be cross-talk among DDB1, Cdh1, and Skp2 in the control of cell cycle division.